Optical properties of AlN thin films grown by plasma enhanced atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2012)
Crystalline aluminum nitride (AlN) films have been prepared by plasma enhanced atomic layer deposition within the temperature range of 100 and 500 degrees C. The AlN films were characterized by x-ray diffraction, spectroscopic ellipsometry, Fourier transform infrared spectroscopy, optical absorption, and photoluminescence. The authors establish a relationship between growth temperature and optical properties and in addition, the refractive indices of the AlN films were determined to be larger than 1.9 within the 300-1000 nm wavelength range. Infrared reflectance spectra confirmed the presence of E-1(TO) and A(1)(LO) phonon modes at similar to 660 cm(-1) and 895 cm(-1), respectively. Analysis of the absorption spectroscopy show an optical band edge between 5.78 and 5.84 eV and the absorption and photoluminescence emission properties of the AlN layers revealed defect centers in the range of 250 and 300 nm at room temperature. (C) 2012 American Vacuum Society. [DOI: 10.1116/1.3687937]